The figure of the doctor and hospitals in the Tradiciones peruanas by Ricardo Palma - Medina Huiza, Eduardo (2019)
This article will analyze the traditions «Los Barbones» and «Los polvos de la condesa». In these texts, it is proposed that Ricardo Palma discusses the figure of the doctor and the hospitals during the viceroyalty.